1980
DOI: 10.3386/w0278
|View full text |Cite
|
Sign up to set email alerts
|

Experience, Performance, and Earnings

Abstract: This study provides direct evidence concerning the relationship between experience and performance among managerial and professional employees doing similar work in two major U. S. corporations. The facts presented indicate that while, within grade levels, there is a strong positive association between experience and relative earnings, there is either no association or a negative association between experience and relative rated performance. If we are correct that the performance ratings given to managerial an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
181
2
3

Year Published

1993
1993
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(194 citation statements)
references
References 0 publications
8
181
2
3
Order By: Relevance
“…The study showed incentive plans resulted in increased revenue and profit and in decreased cost. According to Medoff and Abraham (1980), however, two large manufacturing firms showed that monetary incentive was not closely related to employee performance, despite the firms' merit pay reward systems. The finding of this study is consistent with the study by Banker et al (2001).…”
Section: Resultsmentioning
confidence: 91%
“…The study showed incentive plans resulted in increased revenue and profit and in decreased cost. According to Medoff and Abraham (1980), however, two large manufacturing firms showed that monetary incentive was not closely related to employee performance, despite the firms' merit pay reward systems. The finding of this study is consistent with the study by Banker et al (2001).…”
Section: Resultsmentioning
confidence: 91%
“…In one of the first detailed empirical studies on this topic (Medoff and Abraham 1980), use data from two major US corporations and find evidence that the wages of older workers might be higher than their productivity. Corroborating evidence has been found by Kotlikoff and Gokhale (1992) for workers in US manufacturing industries, Crépon et al (2003) for France, 2 and Haegeland and Klette (1999) for Norway.…”
mentioning
confidence: 99%
“…Evaluators face their own costs of evaluation, including working with disgruntled employees who have received not-so-favorable evaluations, the low opportunity costs of the appraisal work etc. These problems will translate into a tendency of evaluators to assign uniform ratings to employees regardless of performance (Zenger 1992;Medoff and Abraham 1980;Murphy and Cleveland 1995). The resultant rating compression is likely to reduce the effectiveness of subjectivity in providing fair bonus rewards.…”
Section: Determinants Of Subjectivity In Incentive Contractsmentioning
confidence: 98%
“…A typical problem encountered in performance measurement is the tendency of evaluators to assign uniform ratings to employees regardless of performance (Zenger 1992;Medoff and Abraham 1980). Because careful appraisals take time away from betterrewarded activities, and because evaluators face large nonpecuniary costs from disgruntled employees receiving unfavorable appraisals, evaluators have the incentive to shirk their responsibilities (Murphy and Cleveland 1995).…”
Section: Literature On Subjectivitymentioning
confidence: 99%